Integrasi Penataan Pertanahan Dalam Kerangka “Penataan Wilayah Pesisir Dan Lahan Atas Terpadu - Waryanta Waryanta (BHUMI: Jurnal Agraria dan Pertanahan, 2016)
Abstract: Indonesia has the second longest coastline in the world. This condition is considered as a potential to promote thedevelopment of the nations. Nevertheless, some issues emerged related to the development of coastal areas; one of them is thearrangement of the coastal region. The concept of Coastal Zone Planning and Integrated Upper Land Management’is the conceptof sustainable arrangement, integrating land spatial planning and marine spatial planning. This concept is set up to organize anintegrated and comprehensive coastal areas management, including the elements of land and marine water. However, CoastalZone Planning and Integrated Upper Land Management not yet considering the factor of land use, utilization, tenure andownership. To achieve this, it is necessary to set up land use and spatial planning regulations for coastal area, as well as to set upits potential of coastal area planning.Keywords: Coastal, Planning, LandIntisari: Indonesia merupakan salah satu negara yang menempati urutan kedua wilayah pantainya terpanjang di dunia. Hal ini tentumerupakan potensi yang cukup besar untuk mendorong pembangunan di negara ini. Namun demikian, masih banyak persoalan yangdihadapi dalam pembangunan wilayah pesisir, antara lain masalah penataan wilayah pesisir. Konsep “Penataan Wilayah Pesisir danLahan Atas Terpadu “adalah konsep penataan wilayah masa mendatang yang mencoba mengkompromikan antara Rencana Tata RuangWilayah dengan Perencanaan Ruang Laut. Dengan konsep ini diharapkan penataan wilayah pesisir yang melibatkan unsur daratan danperairan laut menjadi integrative dan komprehensif. Namun demikian, perencanaan Penataan Wilayah Pesisir dan Lahan Atas Terpadubelum mempertimbangkan faktor penggunaan, pemanfaatan, pemilikan dan penguasaan tanah. Dan untuk melengkapinya diperlukankebijakan penataan pertanahan di wilayah pesisir dan penyusunan potensi penataan kawasan di wilayah pesisir.Kata Kunci: Pesisir, Penataan, Pertanahan